Survey of Portuguese gynaecologists regarding drug-induced liver injury associates with ulipristal acetate in the treatment of uterine fibroids - Carvalho,Maria João (2021)
Abstract Introduction: Ulipristal acetate (UPA) was introduced in clinical practice for the treatment of uterine fibroids in February 2012. During the post-marketing exposure, there were reports of liver injury and the European Medicine Agency recommended monitoring of liver enzymes for safety reasons. Objectives: The aim of this survey was to gather information about Portuguese gynaecologists’ experience with UPA regarding liver function and other complications related to UPA use. Material and methods: The study consisted of a cross-section survey among members of the Portuguese Society of Gynaecology between April and May 2018. The responders used an online platform to answer a survey that focused on safety and specific alterations in laboratory analyses of liver function considering treatment with UPA since January 2018. Results: In the period considered in this survey, 199 women were treated with UPA by the responders. Monitoring of liver function was performed in 93 women and alterations in liver function laboratory tests were reported in five cases (2.5%). In two of these cases, the past medical history was associated with liver diseases, namely alcoholic, infectious and autoimmune. The clinical course was favourable in all cases. Conclusions: Despite temporary UPA temporary suspension, this survey reinforced the need of clinical database for UPA safety monitoring, particularly regarding the possible application in selected clinical cases.